Wearable Technology & Google Glass: The Next Big Thing? - Chanitra Bishop (Issues in Science and Technology Librarianship)
The article focuses on the application of wearable technologies in higher education and the role of librarians in their use. Wearable devices refer to computers that have been integrated into clothing and accessories. Information is presented on Google Glass, a hands-free smartphone, including privacy concerns about the technology, design and price and how it is being used at the University of California Irvine School of Medicine and Ball State University in Muncie, Indiana.